The Effect of Providing Lecture Recordings on Self-Regulated Learning in Online Learning - Febriani, Vita Indri; Astija (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to examine the effect of providing lecture recordings on students’ self-regulated learning (SRL) in online learning contexts characterized by unstable internet connectivity and limited access to course materials. A quasi-experimental pretest–posttest design was employed involving 52 students from the Biology Education Study Program at Tadulako University, with 26 students assigned to the control group and 26 to the treatment group. SRL data were collected using a questionnaire adapted from the Motivated Strategies for Learning Questionnaire (MSLQ), comprising five subscales: metacognition, time and study environment management, effort regulation, elaboration, and help-seeking. Students in the treatment group received YouTube links to lecture recordings via WhatsApp within 24 hours after each session, whereas those in the control group attended lectures without access to the recordings. Analysis of Covariance (ANCOVA), with pretest scores as the covariate, showed a significant difference in posttest composite SRL scores between the groups (F(1,49) = 32.806; p < 0.001; η²p = 0.401). Significant effects were also found for metacognition (η²p = 0.394), time management (η²p = 0.173), effort regulation (η²p = 0.153), and elaboration (η²p = 0.100), while help-seeking showed no significant difference. These findings suggest that providing lecture recordings through familiar and easily accessible platforms is an effective low-cost pedagogical strategy for enhancing students’ SRL in online learning environments with infrastructural constraints. Therefore, lecture recordings should be considered by lecturers and study program administrators when designing online instruction that supports students’ autonomous learning.